2014
DOI: 10.1007/s10072-014-2010-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum levels of intercellular adhesion molecule-1 and interleukin-6 with migraine

Abstract: To investigate the associations of serum levels of intercellular adhesion molecule-1 (ICAM1) and the pro-inflammatory cytokine interleukin-6 (IL-6) with migraine and migraine subtypes, and to study their correlation with each other in this condition. We used enzyme-linked immunosorbent assay to measure serum levels of ICAM1 and IL-6 in 103 migraine patients with and without aura, in both attack and pain-free periods, and in 100 healthy control subjects. Serum levels of ICAM1 and IL-6 were significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…These data are in line with reported increased levels of several pro-inflammatory cytokines, such as interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-alpha (TNFα) in serum of migraineurs ( Sarchielli et al, 2006 ; Wang et al, 2015 ; Yücel et al, 2016 ). Importantly, plasma levels of pro-inflammatory IL-1α and TNFα are elevated not only in adults but also in children with migraine ( Boćkowski et al, 2009 ).…”
Section: Introductionsupporting
confidence: 78%
“…These data are in line with reported increased levels of several pro-inflammatory cytokines, such as interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-alpha (TNFα) in serum of migraineurs ( Sarchielli et al, 2006 ; Wang et al, 2015 ; Yücel et al, 2016 ). Importantly, plasma levels of pro-inflammatory IL-1α and TNFα are elevated not only in adults but also in children with migraine ( Boćkowski et al, 2009 ).…”
Section: Introductionsupporting
confidence: 78%
“…Observations have shown that in patients with migraine the pro-inflammatory cytokine (IL-1β, IL-6) increases and the levels of anti-inflammatory cytokines (IL-10) decreases [36] reciprocally. Wang et al found that during and in periods of interval of migraine attacks, the serum levels of IL-6 in patients was significantly higher than the healthy control group [37]. Additionally, in vivo studies have shown an increase in the IL-6 mRNA in migraine models [38].…”
Section: Discussionmentioning
confidence: 99%
“…28,[31][32][33][34][35][36]62 The joint effect of these factors may reduce clinical symptoms by enhancing the way in which patients experience pain perception and intensity. 76,77 More investigations are needed to expand our knowledge on the mechanisms of action of behavioral approaches, as well to guide clinicians in choosing the different available behavioral approaches in their daily practice. 31,32,34,46,[66][67][68][69] Improvement in the above-mentioned abilities likely further enhances pain coping strategies and simultaneously promotes reductions in catastrophizing about pain.…”
Section: Discussionmentioning
confidence: 99%
“…63,[71][72][73][74] Furthermore, initial evidence exists on the ability of mindfulness to impact interleukine-6, 75 a marker of inflammation deemed to play a role in the regulation of pain thresholds and to facilitate pain signaling during the development of migraine headaches. 76,77 More investigations are needed to expand our knowledge on the mechanisms of action of behavioral approaches, as well to guide clinicians in choosing the different available behavioral approaches in their daily practice. Research is pointing out that the success of behavioral therapies for pain management is in part due to the success in treating both pain-related behavior and emotions connected to pain.…”
Section: Discussionmentioning
confidence: 99%